PENDAMPINGAN MEDIA DIGITAL STORYTELLING BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN GURU BAHASA INGGRIS SMP TRENGGALEK - Arik Susanti; Anis Trisusana; Zainul Aminin; Fauris Zuhri; Kusumarasdyati Kusumarasdyati; Sumarniningsih Sumarniningsih (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2023)
Education field has provided more space for teachers to be more creative in using technology, as well as being an opportunity to improve students' competence in facing the society 5.0 era. However, social conditions prove that not all teaching staff are able to adapt to the presence of a digital role in the education sector. This workshop was done through several methods, such as observation sheets, scoring rubrics, and questionnaires for pre and post test. The number of participant in this service community was 54 Engliah teachers for junior high in Trenggalek. The results showed that English teachers have experienced improvements in aspects of knowledge and skills related to making digital storytelling media based on local wisdom which can be used as alternative media. It could also improve the quality of teaching and learning. In addition, this service activity would be based on local wisdom considering that the Trenggalek area is a tourist area that is rich in tourist charm and has natural and cultural beauty so that it becomes a new tourist destination in Indonesia. It was concluded that PKM activities can run effectively and efficiently which can be seen in the increased aspects of knowledge and skills. For this reason, it is suggested that English teachers can take advantage of existing culture as an alternative to English teaching materials to attract and motivate students in learning English.